Clinical and immunological characteristics of Aspergillus fumigatus-sensitized asthma and allergic bronchopulmonary aspergillosis - Chen, Hao; Zhang, Xinyu; Zhu, Li; An, Nairui; Jiang, Qing; Yang, Yaqi; Ma, Dongxia; Yang, Lin; Zhu, Rongfei (Frontiers in Immunology, 2022)
Background: Aspergillus fumigatus (A.f) is a common airborne allergen that causes allergic asthma. In a few cases, A.f can colonize in airway and lead to allergic bronchopulmonary aspergillosis (ABPA) in patients. However, the pathogenesis of A.f sensitized asthma and ABPA remains poorly understood. Objective: We aimed at investigate the clinical and immunological characteristics of A.f sensitized asthma and ABPA. Methods: A total of 64 ABPA and 57 A.f-sensitized asthma patients were enrolled in the study, 33 non-A.f-sensitized asthma served as control. The clinical and immunological parameters included lung function, fractional exhaled nitric oxide (FeNO), induced sputum and blood cell analysis, specific IgE/IgG/IgA antibodies and components, cytokines (IL-33, IL-25, TSLP) and CD4+T cell subsets. Results: The eosinophils in blood and induced sputum and FENO were significantly elevated in ABPA patients compared to A.f-sensitized patients. The combination of FeNO and EO parameters presented good diagnostic efficiency in differentiating A.f (+)-asthma from ABPA, with a sensitivity of 80% and a specificity of 100%. A.f-specific IgE, IgG and IgA also increased in ABPA patients. However, serum IL-25, IL-33 and TSLP had no significant differences between the two groups. Cell analysis showed an increasing of IFN-γ+Th1 cells in the ABPA patients. FlowSOM analysis further confirmed that the frequency of CD3+CD4+PD-1+CD127+IFN-γ+T cells was higher in ABPA patients. Conclusion: Our findings suggest the distinct humoral and cell immunologic responses in A.f-sensitized asthma and ABPA patients. ABPA patients have severer eosinophilic inflammation and enhanced Th1 responses compared with A.f-sensitized asthma patients.